1986
DOI: 10.1002/chin.198643223
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reactions of 2‐Chloroalkaneimines with Trialkylphosphites and Triphenylphosphine.

Abstract: Während das 2‐Chlor‐2‐methyl‐N‐butyl‐ l ‐propanimin (II) mit Triethylphosphit (Ib) zu den Phosphonsäureestern (III) und (IV) reagiert, erfolgt bei den Verbindungen (V) sowie (VIIa) und (VIIb) mit (Ia) bzw. (Ib) eine N‐Phosphorylierung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Imidoyl chloride 82 should be less active, as the imine nitrogen atom and trifluoroacetyl group are separated by an oxygen atom (for OCOCF 3 p 0.46 [36] 3 The presence of labile hydrogen atoms in fluoroacetimidoyl chloride 88 offers additional synthetic possibilities. It was shown that its reaction with triethyl phosphite is accompanied by 1,3-prototropic shift to form a mixture (~1:1) of imidoylphosphonates 90a and isomeric C-phosphorylated fluorovinyl amide 91a [38] (Scheme 29).…”
Section: -90%mentioning
confidence: 99%
See 4 more Smart Citations
“…Imidoyl chloride 82 should be less active, as the imine nitrogen atom and trifluoroacetyl group are separated by an oxygen atom (for OCOCF 3 p 0.46 [36] 3 The presence of labile hydrogen atoms in fluoroacetimidoyl chloride 88 offers additional synthetic possibilities. It was shown that its reaction with triethyl phosphite is accompanied by 1,3-prototropic shift to form a mixture (~1:1) of imidoylphosphonates 90a and isomeric C-phosphorylated fluorovinyl amide 91a [38] (Scheme 29).…”
Section: -90%mentioning
confidence: 99%
“…The ratio of the N-and C-phosphorylation products (118/119) is virtually independent of the steric properties of the substituent at the carbonyl group (R = Me or t-Bu), and increases with the electron-withdrawing capacity of the alkoxy group (CF 3 …”
Section: N-acyltrichloroacetimidoyl Chloridesmentioning
confidence: 99%
See 3 more Smart Citations